Effect of disseminated intravascular coagulation on donation after citizens’ death donor kidneys - Xu, Lu (Transl Androl Urol, 2021)
BACKGROUND: To investigate the effect of disseminated intravascular coagulation (DIC) on donor kidney in donation after citizens’ death (DCD) donors. METHODS: The clinical and laboratory data of 159 DCD donors obtained by our center in 2018 were retrospectively analyzed. The DIC diagnosis was performed according to the Chinese DIC scoring system (CDSS). The donors were divided into two groups: DIC (+) and DIC (−). The difference between kidney rejection rate and zero puncture glomerular microthrombus formation rate were compared. RESULTS: Among the 159 DCD donors, 11 were discarded (accounting for 6.91%). The reasons for the discarded cases included 5 cases (3.14%) for moderate and severe glomerular microthrombus formation in the renal zero puncture pathology; 2 cases (1.26%) for glomerular sclerosis ratio over 50%; 2 cases (1.26%) for long-term low blood pressure before pregnancy and significantly increased serum creatinine level and no urine; 1 case (0.73%) for kidney stones and stagnant water; 1 case (0.63%) for malignant tumor. The donor rejection rate of the DIC (+) group was higher than that of the DIC (−) group, and the difference was statistically significant (P<0.05). Among all donors, 10 cases (6.29%) were found to have glomerular microthrombus at zero puncture, and the microthrombotic rate in the DIC (+) group was significantly higher than that in the DIC (−) group (P<0.05). Of the 10 microthrombotic donors, 5 donors with severe glomerular microthrombus were discarded. CONCLUSIONS: Donor-induced DIC can easily cause renal glomerular microthrombus formation, and the donor kidney rejection rate has increased.